Notice of an Ancient Scottish Lectern of Brass, now in the Parish Church of St Stephen's, St Albans, Hertfordshire. (Plate III) (Proceedings of the Society of Antiquaries of Scotland, 1879)
This article sets out the case that a lectern found buried in the grounds of a church in Hertfordshire in 1750 is of Scottish origin. The author argues that the lectern was likely removed from the Abbey Church of Holyrood in 1544 by Sir Richard Lee of Sopwell, who then donated it to the church. The article includes a description of the lectern’s design and the list of documentary evidence that led the author to his conclusions.